Implementasi HOTS-AEP pada Siswa SD dan SMP: Profil Gender Siswa dalam Pembelajaran Lingkungan - Ichsan, Ilmi Zajuli; Sigit, Diana Vivanti; Miarsyah, Mieke; Prayitno, Trio Ageng; Ali, Ahmad; Arif, Wiwin Pramita; Dewi, Aryani Kadarwati; Iriani, Enin; Hermawati, Farah Muthi (Department of Biology Education, Universitas Pendidikan Indonesia, 2019)
In the 21st century learning the ability of Higher Order Thinking Skills (HOTS) is very necessary especially in Environmental Learning. The problem is the unavailability of students' HOTS profiles. The purpose of this study was to describe the HOTS profile of elementary and junior high school students based on gender using Higher Order Thinking Skills Assessment based on Environmental Problems (HOTS-AEP). The study was conducted in July 2019. The sample used was 130 students, consisting of 14 male students and 18 female students at the elementary level. Then, 29 male students and 69 female students for junior high school. The results showed that the overall HOTS score of students were in very low category with the average score of junior high school for male students (17.70) and female (21.10) while elementary school students for male (20.70) and female (23.60). There were differences in scores between elementary and junior high school based on gender. This showed that the ability of HOTS students in environmental learning still needs to be improved. The conclusion was HOTS of female students still higher than male students at the elementary and junior high school. Besides that overall students HOTS are still very low and need to be improved.